Judith Butler and the theology of freedom - Werner, Gunda (Routledge critical studies in religion, gender and sexuality, 2023)
The capillary effect of power in the field of subject theory : theological relevance -- Subjection and control : Michel Foucault's subject theory -- Becoming human in freedom -- becoming a subject according to Judith Butler -- Freedom -- (gender) body -- power (critique) : possibilities and limits of Foucault's and Butler's subject philosophy -- Challenges for a theology of freedom -- Outline of a Theology of freedom.